Residential Care in California: Spatial and Temporal Trends in Facility Development and Care Capacity. (17th December 2021) - Frochen, Stephen; Ailshire, Jennifer; Rodnyansky, Seva; Sheehan, Connor
Abstract: The U.S. is aging, and the older adult population and number of long-term care services are growing but not at corresponding rates and concentrations depending on location. Insufficient research has analyzed residential care at the neighborhood or city level of analysis, where geographical trends in growth often reveal notable patterns of long-term care unobserved at county and state levels of analyses. We merged the California Department of Social Services Residential Care for the Elderly Dataset with census place and tract data to chart the growth of facilities and beds per older adults in all of California and its three largest cities, including 805 facilities licensed from 1996 to 2015. During the study timeframe, residential care steadily increased in California by the number of facilities and beds relative to older adults. However, due to a consistently increasing older adult population, the Cities of San Diego and San Jose experienced gradual and intermittent decline in capacity per older adults, respectively, even as they added many beds to their inventories from the sporadic development of large assisted living and continuing care retirement communities. Additionally, San Jose and Los Angeles exhibited the most overlap in mapping densities of facility development and oldest old adults, with San Diego showing less intersection in cartographic analysis. Understanding facility development and care capacity trends can help local agencies and jurisdictions in the U.S. and other countries discern whether planning policies and other geographical and development factors appropriately encourage the development of residential care and other long-term care facilities.